1973
DOI: 10.1128/jb.113.2.969-984.1973
|View full text |Cite|
|
Sign up to set email alerts
|

Effect of Phosphate Limitation on the Morphology and Wall Composition of Bacillus licheniformis and Its Phosphoglucomutase-Deficient Mutants

Abstract: Volume 113, no. 2, p. 969, column 2, line 10: Change "three poorly lytic (Lyt-) mutants, Lyt-, Lyt--4," to "three poorly lytic (Lyt-) mutants, Lyt--3, Lyt--4,"; lines 21 and 22: Change "a phosphate-deficient medium (26);" to "a phosphate-deficient medium (26) with added sodium citrate (0.05%);". On p. 981, column 2, Table 7: The subheading "Glycerol and galactose" should be under the main heading "6346 his" and the subheadings "Glycerol," "Glycerol and galactose," and "Glucose" should be under the main heading… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
44
0

Year Published

1976
1976
2016
2016

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(45 citation statements)
references
References 33 publications
1
44
0
Order By: Relevance
“…The idea of a surface concentration of anions is also supported by a group of observations which indicate that the typical tribanded wall profile is lost or greatly diminished in preparations where non-peptidoglycan polymers were extracted (1,23,25) or were reduced by a mutational event (9,13). Although extraction of nonpeptidoglycan polymers from walls of several gram-positive species resulted in thinner walls (14,23,25), reduction in width (and volume) was not found to follow a pattern consistent with a layered structure (23).…”
mentioning
confidence: 91%
“…The idea of a surface concentration of anions is also supported by a group of observations which indicate that the typical tribanded wall profile is lost or greatly diminished in preparations where non-peptidoglycan polymers were extracted (1,23,25) or were reduced by a mutational event (9,13). Although extraction of nonpeptidoglycan polymers from walls of several gram-positive species resulted in thinner walls (14,23,25), reduction in width (and volume) was not found to follow a pattern consistent with a layered structure (23).…”
mentioning
confidence: 91%
“…The suppression of only the last stage brought about by various external factors results in long cell chaining in bacteria which have only one plane of cell division (4-6, 20, 22-24) and in cell packeting in bacteria with three planes of division perpendicular to one another (15 , 17, 27). Electron microscopic studies have revealed that individual cells in the long chains are connected by cross walls (6,20). In cell packets, however, the connecting point of individual cells has not been well defined, except that anaerobic sarcinae are known to have a strong tendency to form cell packets (Bergey's Manual, 8th ed.)…”
mentioning
confidence: 99%
“…Culture conditions. B. licheniformis 6346 MH-1 and MH-5 were grown in Spizizen minimal medium supplemented with D-glucose (0.5%) and L-histidine hydrochloride (0.01%) (14).…”
Section: Unpublished Data)mentioning
confidence: 99%
“…Bacillus licheniformis 6346 MH-5 is a derivative of B. licheniformis 6346 MH-1 that lacks phosphoglucomutase and is deficient in active autolysin (14). Both phenotypic changes are thought to be the result of a single genetic lesion (15).…”
mentioning
confidence: 99%